Olive oil's bitter principle reverses acquired autoresistance to trastuzumab (Herceptin™) in HER2-overexpressing breast cancer cells - Brunet Joan; Colomer Ramon; Vazquez-Martin Alejandro; Menendez Javier A; Carrasco-Pancorbo Alegria; Garcia-Villalba Rocio; Fernandez-Gutierrez Alberto; Segura-Carretero Antonio (BMC Cancer, 2007)
Abstract Background A low incidence of breast cancer in the Mediterranean basin suggests that a high consumption of Extra Virgin Olive Oil (EVOO) might confer this benefit. While the anti-HER2 oncogene effects of the main ω-9 fatty acid present in EVOO triacylglycerols (i.e., oleic acid) have been recently described, the anti-breast cancer activities of EVOO non-glyceridic constituents -which consist of at least 30 phenolic compounds-, remained to be evaluated. Methods Semi-preparative HPLC was used to isolate EVOO polyphenols (i.e., tyrosol, hydroxytyrosol, oleuropein). Both the anti-proliferative and the pro-apoptotic effects of EVOO phenolics were evaluated by using MTT-based quantification of metabolically viable cells and ELISA-based detection of histone-associated DNA fragments, respectively. The nature of the interaction between oleuropein aglycone and the anti-HER2 monoclonal antibody trastuzumab (Herceptin™) was mathematically evaluated by the dose-oriented isobologram technique. HER2-specific ELISAs were employed to quantitatively assess both the basal cleavage of the HER2 extracellular domain (ECD) and the expression level of total HER2. The activation status of HER2 was evaluated by immunoblotting procedures using a monoclonal antibody specifically recognizing the tyrosine phosphorylated (Phosphor-Tyr1248) form of HER2. Results Among EVOO polyphenols tested, oleuropein aglycone was the most potent EVOO phenolic in decreasing breast cancer cell viability. HER2 gene-amplified SKBR3 cells were ~5-times more sensitive to oleuropein aglycone than HER2-negative MCF-7 cells. Retroviral infection of the HER2 oncogene in MCF-7 cells resulted in a "SKBR3-assimilated" phenotype of hypersensitivity to oleuropein aglycone. An up to 50-fold increase in the efficacy of trastuzumab occurred in the presence of oleuropein aglycone. A preclinical model of acquired autoresistance to trastuzumab (SKBR3/Tzb100 cells) completely recovered trastuzumab sensitivity (> 1,000-fold sensitization) when co-cultured in the presence of oleuropein aglycone. Indeed, the nature of the interaction between oleuropein aglycone and trastuzumab was found to be strongly synergistic in Tzb-resistant SKBR3/Tzb100 cells. Mechanistically, oleuropein aglycone treatment significantly reduced HER2 ECD cleavage and subsequent HER2 auto-phosphorylation, while it dramatically enhanced Tzb-induced down-regulation of HER2 expression. Conclusion Olive oil's bitter principle (i.e., oleuropein aglycone) is among the first examples of how selected nutrients from an EVOO-rich "Mediterranean diet" directly regulate HER2-driven breast cancer disease.